Exercise, diet, and weight loss - Kiyoji Tanaka; Ryosuke Shigematsu; Tim Henwood; Hiroyuki Sasai (Japanese Society of Physical Fitness and Sports Medicine, 2012)
Japan is one of the most rapidly aging countries in the world. "Healthy Japan 21" is a Japanese government initiative promoting lifestyle-related disease prevention, health promotion, and successful aging. Increasing physical activity participation among older Japanese, the least physically active of any age group, is especially important for preventing frailty and chronic disease, and the associated health care expenditure. Informed by the research we have to date, the following evidence-based conclusions can be drawn relative to exercise and physical activity for the obese population. A combination of aerobic exercise, resistance exercise and physical activities, in addition to proper diet (mostly caloric restriction: 1200 kcal for women and 1680 kcal for men for a certain period of time), is more effective than either form of intervention alone for reducing body weight, visceral fat, blood pressure, and many other negative health-related variables. Exercise habituation in conjunction with proper diet is also most effective for improving vital age. Incorporating and adhering to these lifestyle factors, coupled with adherence to other known health modifiers (reduced stress, improved sleep, etc) will help reduce individual and population obesity and improve national health.